Siedem sztuk wyzwolonych w "Etymologiach" Izydora z Sewilli - Krynicka, Tatiana; Wilczyński, Adam (Vox Patrum, 2023)
Canon of the seven liberal arts belongs to the most prominent achievments of the ancient culture. Ancient thinkers considered them to be sciences worthy of a free person, who dedicates to their studying leisure time, without physical efforts and not for profit-making goals. For Christian writers these are sciences that lead to the discovering of truth which makes a person free. Cassiodorus underlines the fact of their transmission via books (liber) and emphasises their fundamental significance for the human beings’ progress. Isidore of Seville leads his reader to the fascinant world of knowledge through the gates of seven liberal arts as he devotes to them the first three books of his Etymologies. In his discourse on them the grammar occupies the central place (book 1); literary sciences (books 1-2) are presented more profoundly than mathematic disciplines (book 3). Organization of material drawn from his sources is well thought-out, systematic, to some extent original (book 1), in some parts of text (especially those dealing with grammar) somewhat chaotic and incoherent, though. Isidore sums up the role of liberal arts in the ending part of the book 4, while emphasizing that they form the indispensable foundation of doctor’s education.